Maximum levels of hepatitis C virus lipoviral particles are associated with early and persistent infection. (5th July 2016) - Sheridan, David A.; Hajarizadeh, Behzad; Fenwick, Fiona I.; Matthews, Gail V.; Applegate, Tanya; Douglas, Mark; Neely, Dermot; Askew, Bev; Dore, Gregory J.; Lloyd, Andrew R.; George, Jacob; Bassendine, Margaret F.; et al.
Abstract: Background & Aims: Hepatitis C virus (HCV) is bound to plasma lipoproteins and circulates as an infectious lipoviral particle (LVP). Experimental evidence indicates that LVPs have decreased susceptibility to antibody‐mediated neutralisation and higher infectivity. This study tested the hypothesis that LVPs are required to establish persistent infection, and conversely, low levels of LVP in recent HCV infection increase the probability of spontaneous HCV clearance. Methods: LVP in non‐fasting plasma was measured using the concentration of HCV RNA bound to large >100 nm sized lipoproteins after ex vivo addition of a lipid emulsion, that represented the maximum concentration of LVP (maxi‐LVP). This method correlated with LVP in fasting plasma measured using iodixanol density gradient ultracentrifugation. Maxi‐LVP was measured in a cohort of 180 HCV participants with recent HCV infection and detectable HCV RNA from the Australian Trial in Acute Hepatitis C (ATAHC) and Hepatitis C Incidence and Transmission Study in prison (HITS‐p) cohorts. Results: Spontaneous clearance occurred in 15% (27 of 180) of individuals. In adjusted analyses, low plasma maxi‐LVP level was independently associated with spontaneous HCV clearance (≤827 IU/ml; adjusted odds ratio 3.98, 95% CI: 1.02, 15.51, P = 0.047), after adjusting for interferon lambda‐3 rs8099917 genotype, estimated duration of HCV infection and total HCV RNA level. Conclusions: Maxi‐LVP is a biomarker for the maximum concentration of LVP in non‐fasting samples. Low maxi‐LVP level is an independent predictor of spontaneous clearance of acute HCV.